Possibilities for Divine Passibility - Grant, Colin (Toronto journal of theology, 1988)
The winds of modem scepticism about the activity and being of God have been increasingly met by a tack which amounts to a revolution in theological orientation. The classical, transcendent, interventionist understanding of God is replaced by a contemporary immanentist conception that understands the divine nature and activity in terms of a sustaining suffering with the afflicted, as exemplified in the cross. The present intention is to attempt to clarify this development by identifying some of its most prominent sources and suggesting some of its most significant implications. To appreciate these, however, it is necessary to notice just how radical is this change in perspective.